Vicarious structural racism and infant health disparities in Michigan: The Flint Water Crisis - Allgood, Kristi L.; Mack, Jasmine A.; Novak, Nicole L.; Abdou, Cleopatra M.; Fleischer, Nancy L.; Needham, Belinda L. (Frontiers in Public Health, 2022)
Building on nascent literature examining the health-related effects of vicarious structural racism, we examined indirect exposure to the Flint Water Crisis (FWC) as a predictor of birth outcomes in Michigan communities outside of Flint, where residents were not directly exposed to lead-contaminated water. Using linear regression models, we analyzed records for all singleton live births in Michigan from 2013 to 2016, excluding Flint, to determine whether birth weight (BW), gestational age (GA), and size-for-gestational-age (SzGA) decreased among babies born to Black people, but not among babies born to White people, following the highly publicized January 2016 emergency declaration in Flint. In adjusted regression models, BW and SzGA were lower for babies born to both Black and White people in the 37 weeks following the emergency declaration compared to the same 37-week periods in the previous 3 years. There were no racial differences in the association of exposure to the emergency declaration with BW or SzGA. Among infants born to Black people, GA was 0.05 weeks lower in the 37-week period following the emergency declaration versus the same 37-week periods in the previous 3 years (95% CI: −0.09, −0.01; p = 0.0177), while there was no change in GA for infants born to White people following the emergency declaration (95% CI: −0.01, 0.03; p = 0.6962). The FWC, which was widely attributed to structural racism, appears to have had a greater impact, overall, on outcomes for babies born to Black people. However, given the frequency of highly publicized examples of anti-Black racism over the study period, it is difficult to disentangle the effects of the FWC from the effects of other racialized stressors.